2017
DOI: 10.5454/mi.11.1.2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Tempeh Supplementation on the Profiles of Human Intestinal Immune System and Gut Microbiota

Abstract: Tempeh is a traditional fermented soybean product from Indonesia. Although tempeh is consumed as daily menu in Indonesia, its nutrigenomic study employing human has not been reported yet. On the other hand, our study in mice showed that tempeh could enhance immune system, especially by increasing secretory immunoglobulin A production in ileum and colon. Tempeh was also found to be potential in modulating composition of gut microbiota. Therefore, the objective of this study was to analyze the impact of tempeh s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 16 publications
(17 reference statements)
1
16
0
2
Order By: Relevance
“…which the lowest value was found at the end of the study (day 29). This finding was consistent with the previous study, in which 16 days of tempeh consumption increased A. muciniphila production in the human gut (Stephanie et al, 2017).…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…which the lowest value was found at the end of the study (day 29). This finding was consistent with the previous study, in which 16 days of tempeh consumption increased A. muciniphila production in the human gut (Stephanie et al, 2017).…”
Section: Discussionsupporting
confidence: 94%
“…On the following 28 days, soy group consumed 200 mL soymilk per day, while tempeh group consumed 100 grams of tempeh per day. The tempeh was purchased from Empang area, Bogor, which had been previously studied (Barus et al, 2008;Soka et al, 2014;Soka et al, 2015;Stephanie et al, 2017). During the intervention, tempeh was cooked every day according to participants' preferences.…”
Section: Human Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Partial complete of E. coli genome draft in this study will signi cantly contribute further comparative genomic study, especially for E. coli isolates derived from tempeh. Bene cials tempeh supplementation as a paraprobiotics source has been published [7,8], it is reported the whole non-viable might affect human immune and cognitive system. Detail contribution from the tempeh microbial community has not yet been explored.…”
Section: Discussionmentioning
confidence: 99%
“…Tempeh is generally cooked before consumption and might act as a non-viable probiotics source. Previous tempeh nutrigenomic studies showed that cooked tempeh supplementation could enhance the immune system by increasing IgA production in human intestinal tracts [7]. Recently, studies reported cooked tempeh consumption for six months, improving global cognitive function respondents aged 60 years or over with mild cognitive impairment [8].…”
Section: Introductionmentioning
confidence: 99%